Adhesion and osteogenic differentiation of human mesenchymal stem cells on titanium nanopores - S Lavenus; M Berreur; V Trichet; G Louarn; P Layrolle (European Cells & Materials, 2011)
Titanium implants are widely used in orthopaedic and dental surgery. Surface properties play a major role in cell and tissue interactions. The adhesion and differentiation of mesenchymal stem cells were studied as a function of nanostructures. Titanium surfaces with nanopores 30, 150 and 300 nm in diameter were prepared by physical vapour deposition. PCR arrays indicated that the expression of integrins was modulated by the nanopore size. Human Mesenchymal Stem Cells (hMSCs) exhibited more branched cell morphology on Ti30 than on other surfaces. Ti30 and Ti150 induced osteoblastic differentiation while Ti300 had a limited effect. Overall, nanopores of 30 nm may promote early osteoblastic differentiation and, consequently, rapid osseointegration of titanium implants.